Operando X-Ray Imaging of the Charge-Discharge Behavior of Zinc-Air Batteries - Wooseok KANG; Shumpei KUBOTA; Manabu KODAMA; Atsunori IKEZAWA; Hajime ARAI; Shuichiro HIRAI (Electrochemistry, 2024)
Zinc-air batteries are anticipated to be next-generation energy storage devices because of their high capacities compared with conventional secondary batteries. However, the growth of zinc dendrites and electrolyte decomposition can compromise battery performance. To solve those problems, a thorough understanding of electrolyte and electrode behavior is paramount. Therefore, this study employs operando X-ray transmission imaging to observe electrolyte and electrode behavior during charging and discharging, aiming to elucidate their influence on battery performance. Operando X-ray transmission imaging successfully captures bubble generation and zinc deposition in the zinc-air battery. During discharge, bubbles form on the zinc electrode surface through a reduction reaction, while the battery current is suppressed by hindering ion transportation and electrode surface reactions. During charging, a change in the zinc deposition mode is observed from dense deposition to dendrite deposition. This deposition mode change is dependent on the charging current density and zinc ion concentration in the electrolyte. With an increase in the current density and a decrease in the zinc ion concentration, the deposition mode rapidly changes. Through experiments altering both the current density and initial zinc ion concentration in the electrolyte, we effectively determined the operating conditions that hinder zinc dendrite formation.